Effect of adhesive on the anchorage performance of variable curvature waveform clamping anchor for CFRP plate: Experimental investigation and carrying capacity calculation - Yongyu Duo; Minglei Ma; Guowen Xu; Xiaogang Liu (Case Studies in Construction Materials)
As a quintessential anisotropic material, carbon fiber-reinforced polymer (CFRP) plate is characterized by its exceptional longitudinal tensile strength but exhibits poor transverse mechanical performance, which poses significant challenges for effective anchorage. The impact of interface treatment methods and normal pressure on the anchoring performance of variable curvature waveform clamping anchorage (VCWCA) were initially explored in this paper. Then, a carrying capacity calculating method for friction-bending coupling anchoring was established based on the mechanism of the bending effect. Finally, by integrating the friction-bending coupling process with friction-adhesion coupling process, a carrying capacity calculating method for the friction-bending-adhesion coupling anchoring was proposed. The results demonstrated that the anchorage capacity was significantly enhanced with the application of adhesive. Compared to specimens relying solely on friction, the anchorage efficiency of all specimens with adhesive exceeded 95 %. For specimens subjected to friction-bending-adhesion coupling anchoring, the theoretical carrying capacity values were in good agreement with the experimental results, yielding a mean deviation of 3.67 %. The high-efficiency anchorage and the carrying capacity calculating method proposed in this study are expected to provide a solid foundation for the large-scale application of CFRP plates in prestressed reinforcement and cable structures, while also offering a reliable basis for structural design.